Factors Associated with Antenatal Influenza Vaccination in a Medically Underserved Population. (27th January 2020) - Adams, Jenna C.; Biswas, Hope H.; Boulet, Sheree L.; Doraivelu, Kamini; Saums, Michele K.; Haddad, Lisa; Jamieson, Denise J.
Abstract : Influenza infection in pregnant women is associated with increased risk of morbidity and mortality. Despite recommendations for all women to receive the seasonal influenza vaccine during pregnancy, vaccination rates among pregnant women in the U.S. have remained around 50%. The objective of this study was to evaluate clinical and demographic factors associated with antenatal influenza vaccination in a medically underserved population of women. We conducted a retrospective cohort study at Grady Memorial Hospital, a large safety-net hospital in Atlanta, Georgia, from July 1, 2016, to June 30, 2018. Demographic and clinical characteristics were abstracted from the electronic medical record. The Kotelchuck index was used to assess prenatal care adequacy. Relative risks and 95% confidence intervals for associations between receipt of influenza vaccine and prenatal care adequacy, demographic characteristics, and clinical characteristics were calculated using multivariable log-binominal models. Among 3723 pregnant women with deliveries, women were primarily non-Hispanic black (68.4%) and had Medicaid as their primary insurance type (87.9%). The overall vaccination rate was 49.8% (1853/3723). Inadequate prenatal care adequacy was associated with a lower antenatal influenza vaccination rate (43.5%), while intermediate and higher levels of prenatal care adequacy were associated with higher vaccination rates (66.9–68.3%). Hispanic ethnicity, non-Hispanic other race/ethnicity, interpreter use for a language other than Spanish, and preexisting diabetes mellitus were associated with higher vaccination coverage in multivariable analyses. Among medically underserved pregnant women, inadequate prenatal care utilization was associated with a lower rate of antenatal influenza vaccination. Socially disadvantaged women may face individual and structural barriers when accessing prenatal care, suggesting that evidenced-based, tailored approaches may be needed to improve prenatal care utilization and antenatal influenza vaccination rates.